Effect of variable guard time length on mobile WiMAX system performance - Osman, Waiel Elsayed; Abd. Rahman, Tharek (2007)
Guard time length (GT) is one of the key OFDMA parameters. It is implemented as cyclic prefix (CP) to completely alleviate intersymbol interference (ISI) and to preserve orthogonality among OFDMA subcarriers as long as the guard time length is sufficiently greater than channel delay spread. In conventional OFDMA systems a fixed GT length is chosen to be much longer to tolerate worst case condition irrespective of current propagation channel state. This technique, however, degrades the overall spectral efficiency as well as consumes transmitter energy proportional to the length of the guard time. This fact motivates the need to vary the guard time length for mobile applications based on channel parameters. The primary goal of this paper is to investigate the effect of varying the GT length based on channel delay spread for mobile WiMAX technology. The overall system performance and resultant packet error rate (PER) are slightly improved as function of the guard time length.